Selective nonoperative management of penetrating thoracic injury. (February 2018) - Van Waes, Oscar J.F.; Halm, Jens A.; Van Imhoff, Diederik I.; Navsaria, Pradeep H.; Nicol, Andrew J.; Verhofstad, Michael H.J.; Vermeulen, Jefrey
Abstract : Background: Thoracic penetrating injury is a cause for up to one-fifth of all non-natural deaths. The aim of this study was to determine the success of selective nonoperative management (SNOM) of patients presenting with a penetrating thoracic injury (PTI). Methods: This was a prospective study of patients with PTI who presented to a level 1 Trauma Center between April 2012 and August 2012. Results: A total of 248 patients were included in the study, with 5.7% ( n =14) requiring immediate emergency surgery. Overall, five of these 248 patients died, resulting in a mortality rate of 2.0%. Primarily 221 patients (89.1%) were managed with SNOM, of whom 15 (6.8%) failed conservative management. Failure of SNOM was primarily caused by complications of chest tube drainage ( n =12) (e.g. retained clot, empyema) and delayed development of cardiac tamponade ( n =3). The survival rate in the SNOM group was 100%. Conclusion: PTI has a low in-hospital mortality rate. Only 16.5% (41/248) of the patients presenting with PTI will need surgical treatment. The other patients are safe to be treated conservatively according to a protocolized SNOM approach for PTI without any additional mortality. Conservative treatment of patients who were selected for this nonoperative treatment strategy with repeated clinical reassessment was successful in 93.2%.